ENGLISHVET: A NEW METHODOLOGY FOR LEARNING THE ENGLISH LANGUAGE (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
The study of foreign languages is a project from the Federal University of Pampa veterinary PET group that was created in 2012 with the intention of bringing the members of the mentioned project closer to the English language and complement their academic background, inasmuch as it is considered a universal language and has great relevance in the academic field. The project has already had several methodologies, among them: reading and discussion of articles in English, using of learning apps and language course requirement. Nevertheless, some of these methodologies have not been proved effective, making it necessary to implement new measures that would contemplate the study efficiently. The new system, called EnglishVet, has two lines of study, one focuses on basic language level themes, in which the group is divided into pairs or trios, then they study a content according to a pre-established schedule and, based on what was learned, they create a graphic design to be published on the Instagram story. The other line targets specific themes related to veterinary medicine and proposes that the members, individually, study a content pertinent to the course subjects and, then, create a graphic design in dimensions for the Instagram feed. This material is corrected and discussed by the group and by the professors before it is published on the social media. Since the beginning of the project, materials from eight different contents have been published: six of them referring to basic level themes and two related to specific themes, all of it in a period of two months. Based on that, this work aims to analyze the efficiency of the new learning methodology. For this, a test was applied containing 20 objective questions to the 13 members of veterinary PET group, covering all of the contents studied in the eight publications. The grades were divided into four groups: the first one includes only the grades below 6; the second one from 6 to 8; the third one from 8 to 9; and the fourth one is constituted by the grades above 9. Afterward, it was determined that if the grades of most students were concentrated in the group 1, the new methodology would be considered unsatisfactory; in group 2, median; in group 3, good; and in group 4, excellent. The results obtained revealed that the grade of only one student fitted into group 1; five students in group 2; five others in group 3 and two students in group 4. From the analysis of the results, it has been realized that approximately 92% of the grades are median, good and excellent, which allows us to conclude that the new methodology is considered efficient for the language learning of the veterinary PET group members.